Coaching in Brazil sport coaching as a profession in Brazil: An analysis of the coaching literature in Brazil from 2000-2015 - Galatti, L.; Baggiotto Bettega, O.; Zeilmann Brasil, V.; Evanhoé Pereira de Souza Sobrinho, A.; Bertram, R.; Bobato Tozetto, A. V.; Andrade Rodrigues, H.; Collet, C.; Nascimento, J.; Milistetd, M. (International Sport Coaching Journal, 2016)
Sport coaches in Brazil have been recognized as professionals since the implementation of law 9696 in 1998. However, little is known about the impact of this law on the production of coaching science in this country. In an attempt to situate the sports coaching research produced in Brazil since then, the aim of the current study was to show an overview of Brazilian publications from 2000 to 2015. Eight journals were selected and a review was performed in 425 issues of the journals from 2000 to 2015. As a result, 82 published articles were analyzed. On average, five articles were published each year, with 81.7% of the articles published from 2009 to 2015. The findings illustrate that 37.7% of the articles were focused on coaches` thinking and 29.5% on coaches` behaviors, 48.7% used qualitative methods, while 40.3% used quantitative methods and 20.9% used mixed methods. Only two articles attempted to explore the impact of the 1998 legislation on the development of sport coaches in Brazil. In general, research on sport coaching in Brazil seems to be emerging on an international level, as there has been an increase in publications over the past seven years, especially in the lead-up to the Rio2016 Summer Olympic Games.